2005
DOI: 10.1111/j.1365-2052.2005.01367.x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of quantitative trait loci for carcass traits in a Japanese Black (Wagyu) cattle population

Abstract: To detect quantitative trait loci (QTL) that influence economically important traits in a purebred Japanese Black cattle population, we performed a preliminary genome-wide scan using 187 microsatellite markers across a paternal half-sib family composed of 258 offspring. We located six QTL at the 1% chromosome-wise level on bovine chromosomes (BTA) 4, 6, 13, 14 and 21. A second screen of these six QTL regions using 138 additional paternal offspring half-sib from the same sire, provided further support for five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 9 publications
2
24
1
1
Order By: Relevance
“…In agreement with our results, the published growth-related QTL mainly occur in the centromeric section of that region (between markers BM1329 and DIK1054) and involve birth weight (Davis et al, 1998;Casas et al, 2000;Kneeland et al, 2004) and ADG (Kim et al, 2003;Kneeland et al, 2004), whereas published QTL associated with carcass yield and carcass composition have been localized closer to the middle of the chromosome [e.g., QTL affecting LM area, HCW (Casas et al, 2000), and rib thickness (Mizoguchi et al, 2005)]. The simultaneous analysis of birth weight and detailed dissection variables presented here may help to explain the relationship between QTL regions identified in the different cattle populations and correlated effects on these different traits.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In agreement with our results, the published growth-related QTL mainly occur in the centromeric section of that region (between markers BM1329 and DIK1054) and involve birth weight (Davis et al, 1998;Casas et al, 2000;Kneeland et al, 2004) and ADG (Kim et al, 2003;Kneeland et al, 2004), whereas published QTL associated with carcass yield and carcass composition have been localized closer to the middle of the chromosome [e.g., QTL affecting LM area, HCW (Casas et al, 2000), and rib thickness (Mizoguchi et al, 2005)]. The simultaneous analysis of birth weight and detailed dissection variables presented here may help to explain the relationship between QTL regions identified in the different cattle populations and correlated effects on these different traits.…”
Section: Discussionsupporting
confidence: 80%
“…The search for QTL affecting carcass yield and carcass composition in cattle has been mainly conducted by studying commercial half-sib families (Mizoshita et al, 2004;Mizoguchi et al, 2005) or experimental crosses [e.g., Bos indicus × Bos taurus (Stone et al, 1999;Casas et al, 2003) and Limousin × Wagyu cattle (Alexander et al, 2007)]. In the case of experimental cross populations, the QTL model used is based on the assumption that the founder lines are fixed for alternative alleles at the QTL (Haley et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Bovine chromosomes 4 (BTA4) and 14 (BTA14) harbor quantitative trait loci (QTLs) for fat traits, such as marbling score and backfat thickness (Moore et al, 2003;Mizoguchi et al, 2006). Some genes, such as leptin (Stone et al, 1996) on BTA4 and thyroglobulin on BTA14 (Barendse et al, 2001), have been indicated as candidates that can influence these traits, although some of the results are conflicting (Buchanan et al, 2002;Casas et al, 2005;Rincker et al, 2006;Gan et al, 2008;Sherman et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The insulin-like growth factor binding protein 3 gene (IGFBP3) is located at 78.8 cM on BTA4, near a region for the marbling QTL (Mizoguchi et al, 2006). Ballard and colleagues (1988) cloned and characterized six IGFBPs in humans and rodents, which are believed to be similar to those of domestic animals.…”
Section: Introductionmentioning
confidence: 99%
“…In livestock, the major goal of map construction is to dissect the genome to identify genes or chromosomal regions controlling the expression of economically important traits, often called quantitative trait loci (QTL). Numerous experiments have been conducted to detect QTL with promising results for several species, including milk yield and composition, disease resistance, reproduction, growth and carcass traits in beef and dairy cattle (Weller et al, 1990;Van Der Beek et al, 1995;Schrooten and Bovenhuis, 2002, Casas et al, 2004, Gonda et al, 2004, Schnabel et al, 2005, Stone et al, 2005, Mizoguchi et al, 2006.…”
Section: Introductionmentioning
confidence: 99%